Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

convert the polynomial equation y=(x+2)(x-6)(x+7) from factored form to general form

Sagot :

kayt91

y = (x+2)(x-6)(x+7)

(x+2)(x+7)
x^2 - 6x + 2x - 12
x^2 - 4x - 12

(x^2 - 4x - 12)(x + 7)
x^3 + 7x^2 - 4x^2 - 28x - 12x - 84
x^3 + 3x^2 - 40x - 84

y = x^3 + 3x^2 - 40x - 84

[tex]y = (x + 2) (x -6) (x + 7) \\ \\ i.e, y = (x+2) (x^2 - x - 42) \\\\ => y = x^3 + 3x^2 - 40x - 84[/tex]